2012
DOI: 10.1051/0004-6361/201117283
|View full text |Cite
|
Sign up to set email alerts
|

The dust properties of bubble H II regions as seen byHerschel

Abstract: Context. Because of their relatively simple morphology, "bubble" H II regions have been instrumental to our understanding of star formation triggered by H II regions. With the far-infrared (FIR) spectral coverage of the Herschel satellite, we can access the wavelengths where these regions emit the majority of their energy through their dust emission. Aims. We wish to learn about the dust temperature distribution in and surrounding bubble H II regions and to calculate the mass and column density of regions of i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
124
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(138 citation statements)
references
References 104 publications
8
124
0
4
Order By: Relevance
“…There is growing evidence of an inverse relationship between the dust emissivity spectral index, β and the dust temperature, T d (Dupac et al 2003;Désert et al 2008;Paradis et al 2010;Veneziani et al 2010;Anderson et al 2012). We investigate this for the region associated with IRAS 20286+4105.…”
Section: Variation In Dust Emissivity Indexmentioning
confidence: 85%
“…There is growing evidence of an inverse relationship between the dust emissivity spectral index, β and the dust temperature, T d (Dupac et al 2003;Désert et al 2008;Paradis et al 2010;Veneziani et al 2010;Anderson et al 2012). We investigate this for the region associated with IRAS 20286+4105.…”
Section: Variation In Dust Emissivity Indexmentioning
confidence: 85%
“…For the other pointings, with RADEX we only obtain lower limits to the column density, and correspondingly, the average values from the Anderson et al (2012) map are higher than the RADEX values. In particular, pointing C6 shows a large difference between the two estimations, in line with the suggestion made in Sect.…”
Section: Discussionmentioning
confidence: 64%
“…On the other hand, using the column density map obtained by Anderson et al (2012) for RCW 120, we averaged their column density values obtained at the position of the different pointings within the beam of the central pixel of the SLW array (∼36 at 350 μm, Makiwa et al 2013), obtaining the total hydrogen column densities shown in Col. 2 of Table 8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As can be noticed, the emission observed in the three different bands is similar, in the sense that it forms a shell-like structure, instead of having, as observed in several H ii regions, the emission at 70 µm brighter in the interior of the bubble, where the hotter material is expected to be present, and the SPIRE emission, mapping the cooler dust, outside it (e.g. Rodón et al 2010;Deharveng et al 2010;Anderson et al 2012). In this context, the observed largescale distribution of the infrared emission at the periphery of the ionized gas represents matter accumulated during the expansion of the ionized gas.…”
Section: Infrared Emission and Dust Propertiesmentioning
confidence: 73%